Level of Birth Preparedness among Pregnant Women in Allied Hospitals of RMU, Rawalpindi - Khalid, Fatima; Qasim Abbas, Mohammad; Tanvir, Ayesha; Sarwar, Ayesha; Iqbal, Moniba; Kulsoom, Afifa (Students' Supplement of Journal of Rawalpindi Medical College, 2024)
Introduction: Birth preparedness is a comprehensive approach to timely utilization of skilled maternal and neonatal healthcare, addressing high maternal mortality rates in developing countries. Increased awareness about birth preparedness can facilitate early decision-making, ensure safe pregnancies, and minimize delivery-related complications. Objectives: To assess the level of birth preparedness among pregnant women in allied hospitals of RMU and to identify various factors associated with birth preparedness. Materials and Methods: This cross-sectional study involved 270 third-trimester pregnant women from allied hospitals of RMU. Participants completed a self-structured questionnaire. Data analysis was conducted using SPSS version 25, with frequencies and percentages calculated for categorical variables. The Chi-square test determined associations between birth preparedness and numerous factors, with a significance level set at p < 0.05. Results: Of the total 270 pregnant women, 40.7% were found to be prepared for birth. The factors significantly associated with birth preparedness were the mother's education (p=0.045), the husband's occupational status (p=0.012), family income (p=0.000), increasing age of the women (p=0.004), and the last place of childbirth (p=0.016). Conclusions: The level of birth preparedness in Rawalpindi, Punjab, stands at 40.7%. To enhance maternal and neonatal outcomes, it is essential to bolster counseling on the benefits of birth preparedness. This can be achieved through awareness programs led by community health workers.